Cytocompatible magnetostrictive microstructures for nano- and microparticle manipulation on linear strain response piezoelectrics. Issue 1 (5th November 2018) - Xiao, Zhuyun; Khojah, Reem; Chooljian, Marc; Conte, Roberto Lo; Schneider, Joseph D; Fitzell, Kevin; Chopdekar, Rajesh V; Wang, Yilian; Scholl, Andreas; Chang, Jane; Carman, Gregory P; Bokor, Jeffrey; et al.
Abstract: In this work, we investigate polycrystalline Ni and FeGa magnetostrictive microstructures on pre-poled (011)-cut single crystal [Pb(Mg1/3 Nb2/3 )O3 ]1−x -[PbTiO3 ]x (PMN-PT, x ≈ 0.31) with linear strain profile versus applied electric field. Magnetostrictive microstructure arrays with various geometries are patterned on PMN-PT. Functionalized magnetic beads are trapped by localized stray fields originating from the microstructures. With an applied electric field, the magnetic domains are actuated, inducing the motion of the coupled particles with sub-micrometer precision. This work shows promise of using energy-efficient electric-field-controlled magnetostrictive micro- and nanostructures for manipulating magnetic beads via a linear strain response. The work also demonstrates the viability of cells suspended in solution on these structures when subject to applied electric fields, proving the cytocompatibility of the platform for live cell sorting applications.